ETOS KERJA KEPALA SEKOLAH DASAR NEGERI 2 SUKAJAWA TANJUNG KARANG BARAT BANDAR LAMPUNG - Noverlina; Sunarto; Umi Kulsum (UNISAN JURNAL, 2025)
The purpose of this study is to determine the work ethic of the Principal of State Elementary School 2 Sukajawa Tanjung Karang Barat Bandar Lampung. This study is a qualitative study. The sources of research data are primary and secondary data sources. The method of data collection is through interviews, observation and documentation. The steps taken in data analysis are data reduction, data presentation and verification or drawing conclusions. The results of the research data analysis show that the work ethic of the principal is as a coordinator, as a consultant, as a leader, and as an evaluator